Fibromatosis over the dorsa of both feet: An unusual presentation - Y Hari Kishan Kumar; C Sujatha; Sushmitha Jayaprasad (Wolters Kluwer Medknow Publications, 2015)
Fibromatosis is benign fibrous tissue condition intermediate between benign fibroma and metastasizing fibrosarcoma. The lesion tends to infiltrate and recur when removed, but do not metastasize. The lesion may be single or multiple, and the likelihood of recurrence after surgical removal varies with location of the lesion and age. A 40-year-old female presented with multiple raised lesions over both feet since 4 years, they were multiple well-defined firm nodules coalescing to form lobulated plaques distributed in a symmetrical pattern over the dorsum of both feet. Histopathology of skin showed epidermis with hyperkeratosis, acanthosis, mild parakeratosis, and prominent granular layer. Superficial dermis was unremarkable and deep dermis showed thick bundles of irregular collagen and fibroblastic proliferation, suggestive of fibromatosis. This case is being reported for its unusual presentation of fibromatosis over the dorsum of both feet.